On channel estimation and detection for multicarrier signals in fast and selective Rayleigh fading channels. - Yang-Seok Choi
Time-domain channel estimation and detection techniques are presented for multicarrier signals in a fast and frequency-selective Rayleigh fading channel. As a consequence of the time-varying channel, the orthogonality between subcarriers is destroyed in conventional frequency-domain approaches, resulting in interchannel interference, which increases an irreducible error floor in proportion to the normalized Doppler frequency. An important feature of the proposed technique is the ability to exploit the time-selective channel as a provider of time diversity. This enables us to achieve performance superior to any other structure without increasing bandwidth or incorporating redundancy, in order to reduce the complexity of the estimator, we apply the theory of optimal low rank approximation to a minimum mean squared error channel estimator and present a theoretical calculation of mean squared error and simulations to confirm that the estimator is robust to changes in channel characteristics
Keywords: Channel estimation; Fast Rayleigh fading channels; Interchannel interference; Irreducible error floor; Minimum mean squared error channel estimator; Multicarrier signals; Normalized Doppler frequency; Orthogonality; Performance; Redundancy; Selective Rayleigh fading channels; Subcarriers; Time diversity; Time-domain channel estimation; Time-selective channel; Time-varying channel